The apparent diffusion coefficient as a biomarker in the diagnosis of cervical cancer and the assessment of therapeutic response to chemoradiation therapy - Vasić, Jelena; Prvulović Bunović, Nataša; Šarošković, Milica; Vuković, Jelena; Stojanoski, Stefan; Nosek, Igor; Vuković, Miloš (Frontiers in Oncology, 2025)
IntroductionThe apparent diffusion coefficient (ADC) is a significant parameter in the diagnosis and monitoring of cervical cancer. The aim of this study is to evaluate ADC values in patients with cervical cancer, post-therapeutic changes, and normal findings, in order to assess their association with clinicopathological parameters, predict therapeutic outcomes, and differentiate residual tumors from post-treatment tissue without residual disease.MethodsA retrospective study included 148 patients divided into three groups: cervical cancer, post-therapeutic changes and normal findings. ADC values were measured by positioning ROI in the target tissue. Statistical analyses included ANOVA, t-tests, and ROC analysis.ResultsThe mean ADC values for cervical cancer (0.798 × 10-3 mm2/s) were significantly lower compared to post-therapeutic changes (1.394 × 10-3 mm2/s) and normal findings (1.431 × 10-3 mm2/s; p < 0.001). ADC values did not show statistically significant differences based on clinicopathological parameters. The change in ADC values after therapy (ΔADC: 0.607 × 10-3 mm2/s) indicated reduced cellularity. The mean ADC values of residual tumors (1.299 × 10-3 mm2/s) were significantly lower compared to post-therapeutic tissue without residual tumors (1.472 × 10-3 mm2/s; p = 0.029). The optimal value for distinguishing residual tumors from post-therapeutic tissue without residual tumors was 1.436 × 10-3 mm2/s. The optimal value for differentiating pre- and post-therapeutic tumor tissue was 0.929 × 10-3 mm2/s.DiscussionADC proved to be a reliable imaging biomarker for differentiating cervical cancer, post-therapeutic changes, and normal findings, as well as for assessing therapeutic response. It demonstrated significant potential in distinguishing residual tumor tissue from post-treatment changes without residual disease.